Canal contemporâneo: memórias e perspectivas - Canetti, Patricia Kunst (2015)
This work is a survey of Canal Contemporâneo's fourteen years of memory - www.canalcontemporaneo.art.br - and analyzes this memory and its adjacent concepts to point out the prospects of this experiment / research , which reached a surprising longevity in Brazilian cultural Internet. The rescue of its history and collective memory was done in three chapters which thread runs through the editorial sections, platforms and actions of Canal Contemporâneo. In the first chapter we discuss its origin, the first stimuli, concepts and developments. Since then gathered actions that operate in the field of art, politics and communication, pointing to a perspective of narrative and rereading of contemporary art, with a work on Social Netwok Analysis and Data Visualization. The theoretical basis of this research that only begins is based on the following fields and authors: Data Visualization (Fernanda Viégas, Lev Manovich e Manuel Lima); Taxonomy (Marcia Lei Zeng e Jian Qin); Social Netwok Analysis (Katherine Faust e Stanley Wasserman) and models of Random Graphs (Paul Erdős e Alfréd Rényi), Small-World (Duncan J. Watts e Steven Strogatz), Preferential Attachment (Albert-László Barabási e Réka Albert); History and Sociology of Art (Aby Warburg, Alfred Gell e Bruno Latour). We hope that the new shared experience through this work can contribute to a broader view of collection, archiving and cultural heritage, for public policy of culture in Brazil